Determinants of attitude towards credit card usage - Shafinar Ismail; Hanudin Amin; Siti Faseha Shayeri; Nurhaslinda Hashim (Penerbit Universiti Kebangsaan Malaysia, 2014)
Credit cards have been viewed as a competitive banking product that helps to improve a bank’s financial position while at the same time improving financial transactions among customers of a bank. The present study explores the factors influencing the attitude of bank customers in the context of the Malaysian banking system. The study examines the effects of knowledge, media awareness, perceptions, family influence and religious factors on attitudes towards credit card usage. The study finds that knowledge, media awareness, perceptions and family influence are instrumental in determining consumer attitudes toward credit card usage. In more detail, perceptions are ranked highest, followed by family influence and knowledge. Identifying such factors helps to provide better information to direct future planning of credit card services. Importantly, this study provides valuable insight for bank managers to effectively oversee credit card services.